The Effect of Talking Chips On Improving Speaking Skill of S1 Nursing Students - Ahmad Nur Syafiq (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
This study examines the effectiveness of talking chips to improve the S1 Nursing sduents’ speaking skill and its implementation in the English speaking class. This used classroom action research in the way that the data were collected through questionnaire, observation, interview, document analysis and tests. The total samples were 40 S1 Nursing Students of Second Semester including 20 students of intervention group and 20 students of control group which were taken by purposive sampling. Both intervention group and control group were given pre-test to measure the speaking skill before the treatment using talking chips, and then they were given post-test after the treatment. The result of this study showed that there was significant effect of talking chips teaching model to improve the students’s speaking skill which can be seen from pre-test mean score of 49, post test mean score of cycle 1 of 69.3 and the cycle 2 of 77.8. Furthermore, the positive effect of talking chips applied in the class includes the class was more alive, students were motivated to speak in english rather than using Bahasa Indonesia and the class’s interaction was improved significantly.